FOTORESPUESTA DE LAS PELÍCULAS DELGADAS DE ÓXIDO DE Ti PREPARADAS POR "SPUTTERING" - Gómez, Mónica (1999)
Polycristalline Ti oxide this films were prepared by reactive DC magnetron sputtering of Ti in O2+Ar onto Indium Tin Oxide (ITO) coated glass. Rutile and anatase phase films were obtained by heating the substrate during the deposition. Incident photon-to-current efficiency (IPCE) was studied as a function of several sputtering prameters such as temperature of the substraate, film thickness, and O2/Ar. The IPCE increased as the crystallinity of Ti oxide was systematically varied from amorphous to a mixture of anatase and rutile, and it was also enhanced in films deposited at low O2/Ar ratios. The photoresponse was measured using a three-electrode set-up with an electrolyte consisting of an aqueous 0.1 M KI solution purged with nitrogen. Action spectra were scanned between 280 and 400 nm in wavelength. The photogenerate current was found to be highly dependent on the composition thickness, and structure of Ti oxide films.